Enablers and barriers to success among mothers planning to exclusively breastfeed for six months: a qualitative prospective cohort study in KwaZulu-Natal, South Africa - Ngcwalisa Amanda Jama; Aurene Wilford; Zandile Masango; Lyn Haskins; Anna Coutsoudis; Lenore Spies; Christiane Horwood (BMC, 2017)
Abstract Background Exclusive breastfeeding (EBF) for the first six months of life is the most important determinant of child health and development, and is the recommended feeding practice for all mothers. However, EBF rates remain low in South Africa. This study aimed to prospectively explore enablers or barriers to success among mothers who planned to exclusively breastfeed their infants for the first six months of life, in KwaZulu-Natal, South Africa. Methods A qualitative, longitudinal cohort design was adopted. Women were recruited during pregnancy from the catchment area of two hospitals (one urban and one rural) and purposively sampled to include working women, teenagers, and HIV positive pregnant women. This analysis relates to 22 women, from 30 women recruited, who planned antenatally to exclusively breastfeed for six months. These mothers were interviewed monthly for six months postpartum. Infant feeding practices were explored at each visit using in-depth interviews and 24 h feeding recall assessment. Framework analysis was conducted for qualitative data, and quantitative data analyzed using descriptive statistics. Results A total of 125 interviews were conducted between November 2015 and October 2016. Among 22 mothers who planned to exclusively breastfeed for six months, 17 reported adding other food or fluids before six months, and five reported exclusively breastfeeding successfully for the first six months. Key themes showed that all mothers relied strongly on health workers' infant feeding advice and support. All mothers experienced challenges regardless of whether they succeeded in EBF, including inappropriate advice from health workers, maternal-baby issues, pressure from family members and returning to school and work. However, those who were successful at EBF for six months reported that high breastfeeding self-efficacy, HIV status and cultural meaning attached to breastfeeding were underlying factors for success. Conclusion Health workers are key players in providing infant feeding information and support, yet some health workers give mothers infant feeding advice that is not supportive of EBF. Strategies to improve health workers' competency in infant feeding counselling are needed to better prepare pregnant women to overcome common breastfeeding challenges and build mothers' confidence and self-efficacy, thus increasing EBF rates.